2015
DOI: 10.5547/01956574.36.si1.siko
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Prices on Shale Gas Production Strategies

Abstract: In 2014, shale gas accounted for approximately one-third of the U.S. natural gas production as compared to a negligible contribution in 2005, and this share has been increasing despite low energy prices. However, there are concerns regarding the ability of shale production to grow further in the environment of persistently low prices. While production has been growing, the number of drilling rigs has declined (~1,600

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…These results, in general, suggest that prices, infrastructure, and geologic variables play important roles in operators' decisions to complete unconventional gas wells. This is consistent with the results in recent literature where prices and geologic factors are reported to be significant determinants of unconventional oil and gas production decisions (Mason and Roberts, 2018;Kleinberg et al, 2018;Ikonnikova and Gülen, 2015).…”
Section: Duc Duration Status Analysissupporting
confidence: 93%
“…These results, in general, suggest that prices, infrastructure, and geologic variables play important roles in operators' decisions to complete unconventional gas wells. This is consistent with the results in recent literature where prices and geologic factors are reported to be significant determinants of unconventional oil and gas production decisions (Mason and Roberts, 2018;Kleinberg et al, 2018;Ikonnikova and Gülen, 2015).…”
Section: Duc Duration Status Analysissupporting
confidence: 93%
“…Therefore, we complement the HF and FP water study with well-profitability analysis. We use a standard discounted cash-flow model to define how operational profits depend on oil and gas production; energy prices; and costs of processing, transportation, and water handling. , The investment costs are set to depend on drilling depth and length, HF water volumes, and proppant volumes, which are in agreement with the U.S. Energy Information Administration (EIA) report on trends in drilling and completion costs . For 2014, based on operators’ reports, we found that the completion-fluid and flow-back costs are on average about $1 M (million).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Mason and Roberts (2018) consider three margins on which natural gas producers may react to changes in natural gas prices: intra-well production rates, initial-production rate and well-drilling rates, showing that the decline rates of shale wells in Wyoming can be explained by pattern of falling natural gas prices. Ikonnikova and Gulen (2015) look at shale gas productivity changes, focusing on the relationship between gas prices and the completion practices of the industry (namely, the activities necessary for gas to flow after the drilling of a well). Scholars have also noted the dynamics of the DUC wells, which has been rising till spring 2020 then reducing again, investigating their impact on the supply and casting doubt on the drilling-production relationship.…”
Section: Background Literaturementioning
confidence: 99%